2008
DOI: 10.1007/s10551-008-9673-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Identity Salience in the Effects of Corporate Social Responsibility on Consumer Behavior

Abstract: corporate social responsibility, identity attractiveness, relationship marketing, identification, consumer behavior,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
418
1
30

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 527 publications
(473 citation statements)
references
References 64 publications
24
418
1
30
Order By: Relevance
“…Numerous studies have confirmed the influence of perceptions about CSR dimensions on customers' loyalty (Ailawadi et al, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Numerous studies have confirmed the influence of perceptions about CSR dimensions on customers' loyalty (Ailawadi et al, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Socially responsible companies attract, motivate, and retain employees as well as investors (Carroll, 2015;Ćeha, 2013;Geoffrey et al, 2010;Peterlin, Dimovski, Uhan & Penger, 2011). Activities such as caring for the environment, employees, and any kind of help toward the community are becoming important criteria for customers' decision making (Marin, Ruiz, & Rubio, 2009;Srbljinović, 2012). Socially responsible companies have higher productivity due to employees' satisfaction and lower employee fluctuation costs (Kotler & Lee, 2005).…”
Section: Economic Responsibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This research examines how consumers respond to CSR programs that vary in geographic focus. The studies are guided by the extant literature on egocentrism to compare consumer responses to CSR initiatives that are either local or distant; such geographic foci are often components of corporate strategies to demonstrate community attachment and concern for community welfare (Marin et al 2009;Handleman and Bello 2004). The studies also assess the role played by consumers' identity as global citizens and consumers' environmental consciousness as moderators of their generally egocentric tendencies.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Consumers who perceive a company as more socially responsible also maintain higher levels of trust towards the company's products (Pivato et al 2008). Thus, businesses at all levels, but especially at the corporate level, are paying attention to consumers' responses to their CSR strategies (Marin et al 2009;Podnar and Golob 2007).…”
mentioning
confidence: 99%